(untitled) (Research, Society and Development, 2022)
Objective: To analyze the spatial and temporal distribution of notified cases of congenital syphilis in the state of Ceará from 2008 to 2018. Method: Ecological study, with temporal and spatial analysis performed from data on congenital syphilis in the state of Ceará in the period of 2008 to 2018. Results: The number of cases showed an increasing trend, with an inflection point in the year 2012 (AAPC= +12.3; p<0.05). The Moran index showed a positive spatial association for the incidence of congenital syphilis (I = 0.3829) and no spatial association for mortality (I = -0.029; p = 0.303). Conclusion: The growing incidence and the existence of spatial clusters indicate possible weaknesses in the management of syphilis during prenatal care and the need to strengthen actions and training of professionals involved in this care.